Is noise driving job creation? - Schnattinger, P (2020)
This paper studies the effect of noise on the expected value of a firm-worker match in the labour market. In the data, such noise shocks would look like spontaneous increases in labour demand, which cannot rationally be justified by the current and future productivity of the employed worker. A significant amount of noise in the labour market would prevent the correct identification of the response of labour market variables with respect to news shocks. The paper applies the empirical approaches in Blanchard et. al. (2013) and Forni et. al. (2017) to the labour market to estimate the extent to which aggregate job creation is driven by noise rather than news. Based on the estimation of the DSGE model and the structural VAR model using US data, the paper finds that it is unlikely that noise shocks play a significant role in hiring and job creation, as on the aggregate level firms generally anticipate the future output produced by newly hired workers correctly.